China urban poverty and its contributing factors, 1986 - 2000 - Xin Meng; Robert Gregory; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Food price increases and the introduction of radical social welfare and enterprise reforms during the 1990s generated significant changes in the lives of urban households in China. During this period urban poverty increased considerably. This paper uses household level data from 1986 to 2000 to examine what determines whether households fall below the poverty line over this period and investigates how the impact of these determinants have changed through time. We find that large households and households with more non-working members are more likely to be poor, suggesting that perhaps the change from the old implicit price subsidies, based on household size, to an explicit income subsidy, based on employment, has worsened the position of large families. Further investigation into regional poverty variation indicates that over the 1986-93 period food price increases were also a major contributing factor. Between 1994 and 2000 the worsening of the economic situation of state sector employees contributed to the poverty increase. – poverty ; China
Keywords: I32; D31; 330; Städtische Armut; China